Ukrainian flora checklist. 2: family Fabaceae (Fabales, Angiosperms) (CHORNOMORSKI BOTANICAL JOURNAL, 2022)
According to various sources, family Fabaceae Lindl. Has from 730 to 766 genera and from 19 400 to 19 580 species distributed on all continents of the Earth (except Antarctica) and in almost all climatic zones. In Ukraine, there are 70 genera, about 380 natural species together with subspecies, stabilized hybrid forms, described in the status of species. There are 430 natural species together with cultivated in gardens and parks. The most significant nomenclature changes compared to the previous checklist occurred in the genera Astragalus L., Chamaecytisus Link, Genista L., Lotus L., Medicago L., Onobrychis Mill., Securigera DC. The paraphyletic genus Vicia L. has undergone significant nomenclature changes, from which a number of species were transferred to genera Ervilia Link and Ervum L. Instead, the genus Vicia includes V. saxatilis (Vent.) Tropea, isolated from the genus Lathyrus L. (=L. saxatilis (Vent.) Vis.), which is confirmed by comparative morphological and molecular phylogenetic data. Three segregated genera Trifolium L. s. str., Chrysaspis Desv. and Amoria C.Presl were recognized within the genus Trifolium s. l., however alternative names such as Trifolium species are also given.
Keywords: annotated list, species, genera, distribution.